Experience, narrative, and criticism in ancient Greece under the spell of stories - Grethlein, Jonas 1978-; Huitink, Luuk 1981-; Tagliabue, Aldo 1982- (Oxford University Press, 2020)
Drawing on cognitive approaches to literary studies, this volume pursues a new approach to ancient Greek narrative that transcends the taxonomies of structuralist narratologies, deploying concepts such as immersion and embodiment in order to establish a more comprehensive understanding of ancient Greek narrative and ancient reading habits
Includes bibliographical references and index
This edition previously issued in print: 2019
Keywords: Greek literature / History and criticism; Griechisch; Literatur; Erzähltheorie; Aufsatzsammlung